A Rodent Model for Studying Four Well Defined Toxic Endpoints during Bupivacaine Infusion. Issue 4 (July 1991) - Zavisca, Frank G.; Badgwell, J. Michael; Kytta, Juha; Heavner, James E.
Abstract : An animal model with four well defined endpoints for studying the cardiotoxicity and neurotoxicity of bupivacaine is described. Five male Wistar rats (264-324 g) were anesthetized, tracheostomized and ventilated, and ECG and EEG leads were placed. Femoral arteries and veins were then cannulated. Twenty minutes before bupivacaine infusion, 0.1 mg/kg pancuronium was given intravenously, and anesthesia was adjusted to halothane 0.5%, 30% 02 and 70% N2 0. Bupivacaine infusion was then begun at 2 mg/kg/minute. Bupivacaine doses producing the following endpoints were then determined: (1) first ventricular arrhythmia (ARR), (2) seizures (SZ), (3) isoelectric EEG (ISO EEG), and (4) asystole (ASYS). The doses of bupivacaine (in mg/kg ± SD) precipitating ARR, SZ, ISO EEG and ASYS were 4.22 ± 1.87, 7.08 ± 1.55, 11.05 ± 5.15 and 20.4 ± 6.49 mg/kg, respectively. These endpoints were present and readily determined in all animals. The doses of bupivacaine producing ARR and SZ were not significantly different ( p > 0.05). The doses producing SZ, ISO EEG and ASYS were significantly different from each other ( p > 0.05, ANOVA and the Duncan test). These results indicate that it is possible to study, in the anesthetized and paralyzed rat that is intensely monitored, many of the variables associated with local anesthetic toxicity currently of clinical interest. The use of a constant local anesthetic infusion allows ready observation of the progression of toxic signs.